Sir Peter firm on Freedom - Post-Courier (Asia Pacific Network, 1996)
"Three months ago, Archbishop Sir Peter Kurongku delivered an address to the media freedom seminar on the subject of accountability. In his address, he emphasised that the media had responsibility to find and publish the truth. This, he said, was a responsibility placed upon media owners, managers and staff to carry out their duties 'in the service of the community."